1998
DOI: 10.1038/sj.onc.1202352
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of human nucleotide excision repair synthesis in vitro to p21Cdn1

Abstract: The p21 Cdn1 protein (cip1/waf1/sdi1) plays an important role as an inhibitor of mammalian cell proliferation in response to DNA damage. By interacting with and inhibiting the function of cyclin-Cdk complexes, p21 can block entry into S phase. p21 can also directly inhibit replicative DNA synthesis by binding to the DNA polymerase sliding clamp factor PCNA. When cells are damaged and p21 is induced, DNA nucleotide excision repair (NER) continues, even though this pathway is PCNA-dependent. We investigated feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…The LP-BER activity was determined with the repair of R-cccDNA (300 ng) by measuring the incorporation of [a-32 P]-dCTP. Photographs of the autoradiogram is representative of two independent experiments p21-mediated decrease in long-patch BER in plumbagin-treated cells AS Jaiswal et al Shivji et al, 1998). The inhibition of DNA synthesis and cell cycle arrest at G 1 /S phase transition or in S phase has been suggested due to inhibition of PCNA function and Cdk/cyclin kinase activity, respectively, by p21 (Rousseau et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LP-BER activity was determined with the repair of R-cccDNA (300 ng) by measuring the incorporation of [a-32 P]-dCTP. Photographs of the autoradiogram is representative of two independent experiments p21-mediated decrease in long-patch BER in plumbagin-treated cells AS Jaiswal et al Shivji et al, 1998). The inhibition of DNA synthesis and cell cycle arrest at G 1 /S phase transition or in S phase has been suggested due to inhibition of PCNA function and Cdk/cyclin kinase activity, respectively, by p21 (Rousseau et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our target molecules were p21 and PCNA, since both are involved in cell cycle arrest (Cayrol et al, 1998;Dulic et al, 1999;Li et al, 1994b) and DNA repair (reviewed by Dotto, 2000;Jonsson and Hubscher, 1997;Kelman, 1997;Warbrick, 2000;Wilson, 1998). The role of p21 in NER is reported to be through interaction with PCNA; however, it is still unclear whether p21 inhibits (Li et al, 1994a;Shivji et al, 1994Shivji et al, , 1998 or creates resistance to NER (Cooper et al, 1999;Pan et al, 1995). In a recent study, it is suggested that p21 is required for NER at a step located downstream of the recruitment of PCNA to DNA repair sites (Stivala et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Calf thymus DNA polymerase ␦ (Pol ␦; a gift from U. Hübscher, University of Zürich) was purified as described (15), and human proliferating cell nuclear antigen (PCNA) was produced in Escherichia coli (16,17). After annealing to the template, the primer was extended with T7 DNA polymerase (Sequenase version 2.0, United States Biochemical) or Pol ␦ with PCNA, as described (18). Reactions were terminated with sequencing stop buffer (98% deionized formamide͞25 mM Tris-borate-EDTA͞0.025% bromophenol blue͞0.025% xylene cyanol) and loaded onto a 14% denaturing polyacrylamide gel for electrophoresis.…”
Section: Construction Of Covalentlymentioning
confidence: 99%
“…This effect is obtained not only through CDK inhibition, but also by direct binding to the proliferating cell nuclear antigen (PCNA), thereby interfering with PCNA-dependent DNA synthesis, 3,4 while permitting PCNA-dependent DNA repair. 5,6 The dual effect of p21 on cell cycle regulatory proteins is mediated via distinct interaction sites for cyclinCdk complexes and for PCNA. [7][8][9][10][11] In fact, p21 has a CDK binding site in its N-terminal region (aa 53-58), which is distinct from two cyclin binding sites located in the N-and C-terminal regions, [12][13][14][15] respectively.…”
Section: Introductionmentioning
confidence: 99%